Le purgatoire moderne ou la transgression revisitée : la valeur d’usage de Georges Bataille - Krzykawski, Michał (Romanica Silesiana)
The incentive for this essay was “Le retour de Sade” (“The Return of de Sade”), a play by Bernard Noël put on in Paris and Nancy in 2005. The play shows Marquis resurrected by Madame d’Avilla, in the orders of a woman pope who ascends St. Peter’s Throne. De Sade is highly convinced that his descent on the Earth results from his perfectibility in evil and is the proof of his post-mortem triumph. The pope, however, wants to engage him as a court jester because his books are no longer believed to be monstrosities that de Sade thinks they still are. The analysis of De Sade’s resurrection leads to a discussion of Bataille’s concept of eroticism seen as a transgressive act which dispels prohibitions without suppressing them. Referring to Bataille’s essay “The Use of Value of D.A.F de Sade” from 1930, this paper also tries to determine the position of Bataille — a classic French writer whose œuvre was published in the Bibliothèque de la Pléiade, which is considered to be a major sign of recognition for an author in France — in contemporary western culture. The questions that this study attempts to answer are whether Bataille still plays the role of a transgressor and to what extent the transgressive value of Bataille’s eroticism is still attainable in the light of the Foucauldian concept of Power/Knowledge which is inherent in the discourse of sexuality. Key words: Pornography, eroticism, sexuality, transgression.